Conventional En Masse Repair Versus Separate Double-Layer Double-Row Repair for the Treatment of Delaminated Rotator Cuff Tears. (May 2016) - Kim, Yang-Soo; Lee, Hyo-Jin; Jin, Hong-Ki; Kim, Sung-Eun; Lee, Jin-Woo
Background: The rotator cuff tendon is known to exert a shear force between the superficial and deep layers. Owing to this characteristic, separate repair of delaminated rotator cuff tears has been introduced for the restoration of the physiological biomechanics of the rotator cuff. However, whether conventional en masse repair or separate repair is superior is controversial in terms of outcomes. Purpose: To compare clinical outcomes between conventional en masse repair and separate double-layer double-row repair for the treatment of delaminated rotator cuff tears. Study Design: Randomized controlled study; Level of evidence, 2. Methods: Between August 2007 and March 2014, a total of 82 patients who underwent arthroscopic rotator cuff repair of a delaminated tear were enrolled and randomized into 2 groups. In group 1 (n = 48), arthroscopic conventional en masse repair was performed. In group 2 (n = 34), separate double-layer double-row repair was performed. The American Shoulder and Elbow Surgeons score, Constant score, Simple Shoulder Test score, and visual analog scale (VAS) score for pain and range of motion (ROM) were assessed before surgery; at 3, 6, and 12 months after surgery; and at the last follow-up visit. Magnetic resonance imaging (MRI) was performed at 12 months postoperatively to examine the retear rate and pattern. Results: There was no significant difference between groups in the preoperative demographic data, including patient age, sex, symptom duration, tear size, and functional scores ( P > .05). The mean follow-up period was 25.9 ± 1.2 months. Significant improvements in functional and pain scores were observed in both groups at the last follow-up visit. However, no significant differences in functional scores and ROM were found between the 2 groups at each time point, except that group 2 had significantly lower VAS pain scores ( P < .05) at 3, 6, and 12 months postoperatively. Eight (17%) of 48 patients in group 1 and 6 (18%) of 34 patients in group 2 showed retears on MRI at 12-month follow-up ( P > .05). Conclusion: Both conventional en masse repair and separate double-layer double-row repair were effective in improving clinical outcomes in the treatment of delaminated rotator cuff tears. Lower pain scores were seen in patients who underwent separate double-layer double-row repair.